Headquarters parenting advantage in Chinese MNEs: The moderating role of top managers' political and International experience. Issue 2 (April 2023) - Su, Cong; Ciabuschi, Francesco; Kong, Lingshuang
Highlights: HQ parenting advantage in international value-adding activities exists in Chinese MNEs. HQ involvement enhances the extent of reverse knowledge transfer in Chinese MNEs. TMT political experience weakens the effect of HQ involvement on reverse knowledge transfer. TMT international experience strengthens the effect of HQ involvement on reverse knowledge transfer. Abstract: This study explores the relevance of top management teams' experience to support the headquarters parenting advantage in the context of Chinese multinationals. Specifically, it studies how the political and international experience of headquarters' top management teams moderates the relationship between headquarters involvement in knowledge transfer processes – a key aspect of value creation in the parenting advantage logic – and the extent of reverse knowledge transfer from subsidiaries. Based on the data from two complementary surveys of senior managers in 99 Chinese multinationals and managers in their 177 subsidiaries, our analysis indicates a contrasting effect of top managers' experience as their political experience weakens, but their international experience strengthens the positive effect of headquarters involvement in reverse knowledge transfer. This study contributes to the parenting advantage logic, by introducing the relevance of different top managers' experiences, and to our understanding of top management teams in the context of both reverse knowledge transfer and Chinese multinationals, particularly by showing the important implications of top management teams' experience for Chinese enterprises' international strategies.